2017
DOI: 10.1007/s11158-016-9349-7
|View full text |Cite
|
Sign up to set email alerts
|

Egalitarianism and the Great Recession: A Tale of Missed Connections?

Abstract: The main aim of this paper is to act as a corrective to the comparatively deafening silence of egalitarian political philosophy's response to the Great Recession. The paper thus provides an accessible analysis of a new strand of empirical research into the causes of the crisis. This new literature, which has largely gone unnoticed by the broader philosophical community, maintains that the main driver of financial instability is income and wealth inequality coupled with income stagnation at the bottom of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…In relation to the economic dimension of green growth, preliminary empirical literature studied the stability-growth nexus through the financial-led growth hypothesis. The wide-ranging literature (Goldsmith, 1969; McKinnon, 1973; King and Levine, 1993; Rajan and Zingales, 1998; Levine et al , 2000) found a positive impact of FS on economic growth. Most recently, Denk and Cournède (2015) has also found a positive relationship between financial development and economic growth in the long run and he suggested that financial development is the main driver of causality in economic growth in the cross country analysis of Organization for Economic Cooperation and Development (OECD) countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In relation to the economic dimension of green growth, preliminary empirical literature studied the stability-growth nexus through the financial-led growth hypothesis. The wide-ranging literature (Goldsmith, 1969; McKinnon, 1973; King and Levine, 1993; Rajan and Zingales, 1998; Levine et al , 2000) found a positive impact of FS on economic growth. Most recently, Denk and Cournède (2015) has also found a positive relationship between financial development and economic growth in the long run and he suggested that financial development is the main driver of causality in economic growth in the cross country analysis of Organization for Economic Cooperation and Development (OECD) countries.…”
Section: Literature Reviewmentioning
confidence: 99%